#TITLE_ALTERNATIVE# - DEFFINIKA (NIM 10105002), PRIMA
This final project discuss about the effects of sea bottom's characteristic as a porous medium, flow characteristic, and sea bottom's topography to generate the surface waves. The mathematical model for the elevation of a free surface is derived from two boundary value problems in which each problem represents flow in different medium. The model is solved numerically by Finite Difference Method with Predictor-Corrector scheme. A flow in a fluid medium generates the surface waves because the flow is disturbed by un-flat surface of the porous medium. The obtained mathematical model able to explain the physical phenomena for steady flow case. The existence of porous medium influences in decreasing the amplitude of the generated waves, and for long run steady waves has shifted phase from topography of the interface (confluence of two media, fluid medium and porous medium). The shifted phase depends on the characteristic of porous medium, flow, and the topografy of the interface.